Efecto del suplemento energético y proteico en la población de abejas (Apis mellífera) en épocas de escasez de floración e incidencia en la producción de miel - Guaya Galindo, Pablo José (2016)
The following project was carried out in the community of “El Tambo”, Canton of Zamora the same is located 35km from the city of Loja near the San Francisco Scientific Station, with the purpose of evaluating a feeding system in time of shortage of flowering in order to optimize production in times of honeydew in this area. Eight hives were used each beehive was n experimental unit which were divided into two groups of four hives each, on the first treatment (T1) energy supply was used (sugar syrup) while the second treatment (T2) besides the sugar syrup a record of provision of protein food prepared with cornmeal, soybeans and oat portions of 400g per hive. Obtaining the following results: the consumption of protein food got an average 542g per hive, an average consumption of sugar syrup treatment 9.8875,5 ml in the control treatment and 10.125 ml on the experimental treatment an average of 14,03 frames with abundant bee; on the witness treatment while on the experimental treatment recorded 15.64 frames with abundant bee; an average of 4.97 frames with one treatment breeding and rearing 6,75 frames with the second treatment; with queen existence on both treatments during the whole investigation process. We can conclude that the type of food affects both the evolution of the population and the profitability of the honey production.